2017
DOI: 10.1039/c7fo00842b
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dietary magnesium and caseinphosphopeptides on bone metabolism in rats

Abstract: The effect of dietary magnesium (Mg) or caseinphosphopeptides (CPPs) on bone metabolism has been reported. However, few studies have investigated the effects of simultaneous supplementation of Mg and CPPs. Sixty-three 3-week-old Sprague-Dawley male rats were divided into seven groups and fed a specified diet for 45 days. Body characteristics, bone physicochemical indicators, and bone metabolism indicators relative to bone metabolism were analyzed. We found that, first, a dietary Mg deficiency resulted in incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Mineral supplements can be beneficial in preventing or treating bone diseases with bone loss [ 38 , 39 ]. For example, Liu et al [ 40 ] showed that Mg supplementation prevented bone resorption and increased bone formation in growing male rats [ 40 ]. Similarly, a meta-analysis study reported increased BMD (r 0.16, 95% CI 0.001) in humans associated with Mg consumption [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mineral supplements can be beneficial in preventing or treating bone diseases with bone loss [ 38 , 39 ]. For example, Liu et al [ 40 ] showed that Mg supplementation prevented bone resorption and increased bone formation in growing male rats [ 40 ]. Similarly, a meta-analysis study reported increased BMD (r 0.16, 95% CI 0.001) in humans associated with Mg consumption [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, as caseins could promote bone formation and body development by increasing intestinal calcium absorption and bioavailability [14,[26][27][28]49], the effect of this 11-bp indel of the CSN1S1 gene on the body measurement traits of goats is worth studying. The association analysis results demonstrated that this polymorphism significantly affected the body measurement traits of goats and affected the different body measurement sizes in different goat breeds (Table 3; p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that Mg 2+ can significantly affect the proliferation and differentiation of osteoblast cells by stimulating hormone secretion or cytokine synthesis. [88][89][90] Many reports have proved that Mg and Mgdoped implants can promote osteoblastic cell adhesion and bone regeneration. [91][92][93] In an in vitro assay, the Mg-CDs exhibited low cytotoxicity to mouse embryo osteoblast precursor cells (MC3T3-E1).…”
Section: Osteogenesismentioning
confidence: 99%